Identification and Screening of Individuals at Increased Risk for Pancreatic Cancer with Emphasis on Known Environmental and Genetic Factors and Hereditary Syndromes - Chu, David; Kohlmann, Wendy; Adler, Douglas G (JOP. Journal of the Pancreas, 2010)
Despite recent diagnostic and therapeutic advances, pancreatic cancer still carries a poor prognosis. Screening high-risk individuals is a relatively new concept with regards to pancreatic cancer but is an area of intense study. Significant effort has been invested in identifying risk factors for pancreatic cancer. Risk factors for pancreatic cancer can be classified into three broad categories: demographic, environmental (host), and hereditary (genetic) predisposition. This manuscript will review the risk factors and genetic syndromes associated with increased risk of developing pancreatic cancer, the role of genetic testing in the evaluation of high-risk patients, the available serologic and imaging tests that can be used to screen these individuals, and will summarize the available literature on attempts at pancreatic cancer screening to date. Image: Logo of Huntsman Cancer Center, University of Utah School of Medicine. Salt Lake City, UT, USA